How the news was made: the anti-social behaviour day count, newsmaking criminology and the construction of anti-social behaviour - Edwards, Phil (Critical criminology, 2013)
‘Newsmaking criminology’ is an approach to criminological research characterised by critical engagement with topics being covered by the news media, offering greater engagement with public debate and reflexive critique of the objects of criminological knowledge. Two examples of Brisith criminological researchers taking an identifiable ‘newsmaking’ approach are discussed in this paper: the Anti-Social Behaviour One Day Count, a 24-h comprehensive survey of reports of anti-social behaviour carried out in 2003, and the 24-h Domestic Violence Audit, carried out in 2000. This paper analyses the construction of knowledge of anti-social behaviour through the Day Count, identifying continuities and discontinuities between the Day Count and the Domestic Violence Audit. This leads to a discussion of the strengths and limitations of the ‘newsmaking’ approach, suggesting that it may serve conservative as well as progressive ends.